ELEMEN INTERIOR SEBAGAI SPOT SELFIE PADA KAFE- KAFE INSTAGENIC DI KOTA DENPASAR - Dewi, Putu Surya Triana (SENADA (Seminar Nasional Manajemen, Desain dan Aplikasi Bisnis Teknologi), 2018)
The phenomenon of selfie has become a commonplace in today's era. This is what triggers the emergence of 'Instagenic' cafes and encourage existing cafes on the island of Bali to be better. Some of them by inserting the selfie spot, rearranging the cafe interior so more instagramable, in order to seize the market. Instagenic or Instagram - photogenic in question is a term for interesting and photogenic visual content if uploaded to social media Instagram the latter on the rise. In the present era, there was an unconscious addition of front-of-the house area of the café facilities in Denpasar in the form of a selfie spot. Selfie spot is not necessarily in the form of special space such as dining area, this selfie spot blend as aesthetic elements of space. The results of the questionnaire showed four types of aesthetic elements in the cafe that encouraged the respondents to do selfie, including wall decoration, lighting, furniture, and signage / café logo. Wall decoration became the favorite of respondents as a selfie spot at instagenic cafes in Denpasar city.